1994
DOI: 10.1002/mc.2940110204
|View full text |Cite
|
Sign up to set email alerts
|

Induction of specific cytochrome P450s involved in aflatoxin B1 metabolism in hepatitis B virus transgenic mice

Abstract: The relative roles of hepatitis B virus (HBV) and aflatoxin and their possible mechanism of interaction in the etiopathogenesis of hepatocellular carcinoma (HCC) are not understood. One hypothesis is that viral infection and associated liver injury alter expression of carcinogen-metabolizing enzymes. We tested this hypothesis in an HBV-transgenic mouse model in which a synergistic interaction occurs between aflatoxin B1 (AFB1) and HBV in the induction of HCC (Sell et al., Cancer Res 51:1278-1285, 1991). In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
58
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 18 publications
5
58
1
Order By: Relevance
“…41 Although injection of AFB 1 after weaning (1 month of age) is not carcinogenic for nontransgenic C57BL/6 mice, 25,26 in a previous study, AFB 1 -treatment of lineage 50-4 female mice at 3 months of age resulted in accelerated tumor development. 34 This was unexpected because liver injury and increased cellular proliferation associated with retention of HBsAg in transgenic mice does not occur until after 6 months of age.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…41 Although injection of AFB 1 after weaning (1 month of age) is not carcinogenic for nontransgenic C57BL/6 mice, 25,26 in a previous study, AFB 1 -treatment of lineage 50-4 female mice at 3 months of age resulted in accelerated tumor development. 34 This was unexpected because liver injury and increased cellular proliferation associated with retention of HBsAg in transgenic mice does not occur until after 6 months of age.…”
Section: Discussionmentioning
confidence: 92%
“…There is increased expression and altered distribution of Cyp2a-5 in transgenic mice expressing HBsAg, and the increase in Cyp2a-5 correlates with the development of liver injury in mice and with age. 41 Cyp2a-5 is a highly conserved mouse cytochrome P450 isoenzyme that is important in AFB 1 metabolism and shares homology and catalytic properties with human CYP2A6. In addition, Cyp-3a, which is another P450 enzyme involved in AFB 1 metabolism was shown to also be increased in HBV-transgenic mice, but the increase was not clearly related to age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic mice harboring the gene for HBV surface antigen develop a progressive liver injury caused by accumulation of the antigen, and a concomitant emergence of CYP2A5-positive hepatocytes can be observed throughout the acinus. 18 In the HBV transgenic mouse lineage 107.5, HBV surface antigen is expressed at noncytopathic concentrations, but, when treated with a cytotoxic T-lymphocyte clone, the mice develop a severe necroinflammatory liver disease that is accompanied by CYP2A5 induction. 38 Increased CYP2A expression is also present at the periphery of cirrhotic nodules caused by O. viverrini infestation in hamster livers.…”
Section: Discussionmentioning
confidence: 99%
“…3,15,16 Animal studies have also shown that the expression of hepatic CYP2As is up-regulated by various types of biological insults, such as infestation with the liver fluke Opisthorchiasis viverrini 17 and integration of hepatitis B virus (HBV) to hepatocyte DNA. 18 In these animal models, CYP2A induction is associated with chronic inflammation in the liver tissue. In addition, liver tumors in mice contain highly elevated levels of CYP2A5.…”
mentioning
confidence: 99%